Production method for electrically growth-promoted selenium-rich anticancer spinach - JIAO QINGHUA; QIU JIANMEI; QIU JINMING; QIU JIANFENG (2010)
The invention provides a production method for electrically growth-promoted selenium-rich anticancer spinach, belonging to the application study of the white agricultural high technology in the field of the nutritious dietetic food production technology. The production method is composed of a known spinach production facility, a selenium-rich microelement fertilizer employing technology and a high-voltage pulse positive-ion growth promoting machine. The spinach production facility means a spinach production greenhouse or an open-air vegetable field. The selenium-rich microelement fertilizer means one of sodium selenite, potassium selenite and sodium selenate or the combination of the above. The employing quantity of the fertilizer per acre is within 1 to 15g, and the fertilizer needs to be diluted by water to the concentration of 1/1,000 to 1/100,000 (weight). The using method of the fertilizer is as follows: the fertilizer can be used for soaking seeds and can be employed on leaf surfaces in growth period fo